Maximizing Participation in Corporate Volunteering - Michael Verbücheln; Laura Marie Edinger-Schons (Marketing Review St.Gallen, 2020)
Companies increasingly use corporate volunteering programs to bring purpose to their employees' work lives and offer attractive job products. Still, challenging questions remain concerning the right design and effective communication of these programs. This article provides answers to these questions to maximize employee participation in corporate volunteering.
Keywords: 650